1999
DOI: 10.1191/096032799678839473
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen reactive radicals production in cell culture by okadaic acid and their implication in protein synthesis inhibition

Abstract: Okadaic acid (OA), a diarrhetic shellfish toxin is a potent promoter of tumours in mouse skin and a specific inhibitor of protein phosphatases 1 and 2A. Recently it has been shown that OA inhibited protein synthesis in a cell-free system, with 50% inhibitory concentration of 6.3610712 M but the mechanism whereby this inhibition is mediated was still unclear. In the present study, the effect of OA on protein synthesis in Vero cell cultures was investigated. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 24 publications
0
18
1
1
Order By: Relevance
“…Thus our own previous data, together with the findings by other investigators that OA-induced apoptosis is associated with downregulation of Bcl-2 and can be prevented by upregulation of Bcl-2 (Benito et al, 1997;Nuydens et al, 2000;Cabado et al, 2004), suggest that Bcl-2 plays an important role in the neuroprotective effects of olanzapine on OA-induced neurodegeneration and apoptosis. Olanzapine may also attenuate OA-induced neurotoxicity by upregulating superoxide dismutase (Manna et al, 1998;Li et al, 1999;Matias et al, 1999), and perform protective effects on OA-induced apoptotic cell death by modulating the expression of pro-and antiapoptotic proteins such as Bax and Bcl-X L (Wei et al, 2003b;Cabado et al, 2004). However, further studies are necessary to elucidate whether olanzapine attenuated OA-induced neurotoxicity by directly affecting the activation of phosphatases or caspases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus our own previous data, together with the findings by other investigators that OA-induced apoptosis is associated with downregulation of Bcl-2 and can be prevented by upregulation of Bcl-2 (Benito et al, 1997;Nuydens et al, 2000;Cabado et al, 2004), suggest that Bcl-2 plays an important role in the neuroprotective effects of olanzapine on OA-induced neurodegeneration and apoptosis. Olanzapine may also attenuate OA-induced neurotoxicity by upregulating superoxide dismutase (Manna et al, 1998;Li et al, 1999;Matias et al, 1999), and perform protective effects on OA-induced apoptotic cell death by modulating the expression of pro-and antiapoptotic proteins such as Bax and Bcl-X L (Wei et al, 2003b;Cabado et al, 2004). However, further studies are necessary to elucidate whether olanzapine attenuated OA-induced neurotoxicity by directly affecting the activation of phosphatases or caspases.…”
Section: Discussionmentioning
confidence: 99%
“…In cultured rat cortical neurons, OA may induce cell death by increasing phosphorylation of microtubuleassociated protein 2 and tau concomitant with early changes in the neuronal cytoskeleton (Arias et al, 1993). OA may also induce cellular injury and death by inactivating Bcl-2 by phosphorylation (Haldar et al, 1995), activating caspase-3 (Hong et al, 2002), or forming high reactive free radicals (Matias et al, 1999) in vitro. Infusion of OA into the rat brain results in severe memory impairment, accompanied by remarkable neuropathological changes including hippocampal neurodegeneration, a paired helical filament-like phosphorylation of tau protein, and the formation of b/A4-amyloid containing plaque-like structures in gray and white matter areas (Arendt et al, 1995(Arendt et al, , 1998Zhao et al, 1995;He et al, 2001;Tian et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are in full agreement with this hypothesis. The reactive oxygen species produced also contribute to the cytotoxicity of OA (Matias et al, 1999a;Traoré et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…OA is known to be a potent inhibitor of serine/ threonine phosphatases (Bagu et al, 1997;Biolojan and Takai, 1998) and a specific inhibitor of protein synthesis through hyperphosphorylation of elongation factor EF2 (Matias et al, 1996(Matias et al, , 1999a. Matias and Creppy (1998) showed that at low concentrations, OA increases DNA bases oxidation and methylation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation